ANALISIS DEFECT PACKAGING PUPUK DENGAN METODE STATISTICAL QUALITY CONTROL DAN FAILURE MODE AND EFFECT ANALYSIS PADA INDUSTRI PUPUK DI CV. XYZ - Muhana Naufal Susilo; Suseno Suseno (KAMPUS AKADEMIK PUBLISING, 2026)
. CV. XYZ is a company that produces 50 kg NPK fertilizer packaging and still experiences packaging defects, particularly sewing defects and weighing defects. This study aims to analyze quality control, identify the causes of defects, and determine improvement priorities using Statistical Quality Control (SQC), Fishbone Diagram, and Failure Mode and Effect Analysis (FMEA). The data used were collected from February23 to April 14, 2026, with a total production of 2,739 bags and 580 defective bags,consisting of 459 sewing defects and 121 weighing defects. The results of the p-controlchart indicate that the process is not yet statistically controlled, as shown by severalpoints falling outside the control limits for sewing defects (CL = 0.168, UCL = 0.189,LCL = 0.146) and weighing defects (CL = 0.044, UCL = 0.056, LCL = 0.032). Fishboneanalysis revealed that the causes of defects originated from human, machine, method,material, and environmental factors. The FMEA results showed that the highest RiskPriority Number (RPN) values for sewing defects were machine malfunction (280) andloose thread (210), while for weighing defects they were improper gate valve settings(240) and fertilizer accumulation in the hopper (192). The proposed improvementsinclude implementing preventive maintenance, inspecting the gate valve, checkingthread conditions, and controlling fertilizer flow and hopper capacity to reduce defectrates and improve product quality.